Mobilizing Financing for Climate Smart Investments in the Mekong Delta : An Options Note - World Bank (World Bank, Hanoi, 2020)
The Mekong Delta in Vietnam covers approximately 12 percent of the national area, and is home to approximately a fifth of Vietnam’s population. The region contributes 50 percent of the rice crop, 65 percent of aquaculture, 70 percent of fruit, 95 percent of exported rice and 60 percent of exported fish. There are considerable opportunities for further development of the Mekong Delta region. Unlocking these opportunities will require addressing several existing challenges. The challenges stem from, among other things, inadequate infrastructure and market access, fluctuations in water availability, weak interprovincial coordination, climate change, pollution, and energy constraints. The Mekong Delta of Vietnam is also extremely vulnerable to climate change.